The impact of health on professionally active people's incomes in Poland. Microeconometric analysis; Wpływ stanu zdrowia na dochody osob́ aktywnych zawodowo w Polsce. Analiza mikroekonometryczna - Iwona Laskowska (Comparative Economic Research. Central and Eastern Europe, 2010)
In contemporary world human capital is one of the basic elements of development. In a broad understanding it means "the resource of knowledge, skills, health and stamina in the society" (Domanśki, 1993). Health, besides education, is one of the determinants of its quality. It determines work efficiency, physical and intellectual development, and conditions the average lifespan. It is the resource influencing the functioning of individuals, enterprises - having a connection with their competitiveness - and the whole economy. The impact of health on economic processes may be observed both on macroscale level and on the level of individuals. In the presented research an attempt was made to verify the hypothesis that the state of health is one of the factors determining professionally active people's incomes. It was assumed, that there is a possibility of the health state impact on decreasing incomes, not only on their complete loss. In the analysis the micro data gathered in the research "Social Diagnosis 2009" were used. The function was estimated basing on Mincerian wage equation with the logarithm of personal income as a dependent variable and respondents characteristics (gender, work experience, practiced profession) as independent variables. Above all, however, variables connected with respondents health were included in the model. The outcome of the research confirms the occurrence of positive interaction between professionally active people's incomes and the self-assessed state of health. People declaring a bad state of health have incomes by 20% on average lower than people who enjoy good health (assuming that the remaining characteristics of the surveyed person are the same). In case of men, the impact of health state on incomes is slightly greater than in case of women. – – We wspoĺczesnym sẃiecie jednym z podstawowych czynnikoẃ rozwoju jest kapitał ludzki, w szerokim rozumieniu oznaczajacy "zasob́ wiedzy, umiejetnosći, zdrowia, energii witalnej zawartej w społeczenśtwie" (Domanśki, 1993). Zdrowie, obok edukacji, stanowi zatem jeden z wyznacznikoẃ jego jakosći. Determinuje wydajnosćṕracy, rozwoj́ fizyczny, emocjonalny i intelektualny człowieka, warunkuje przecietna długosćźẏcia. Stanowi zasob́ wpływajacy na funkcjonowanie poszczegoĺnych osob́, przedsiebiorstw-poprzez zwiazek z ich konkurencyjnosćia- oraz całej gospodarki. Wpływ zdrowia na procesy ekonomiczne mozė bycóbserwowany w skali makro i na poziomie jednostek. W prezentowanych badaniach podjeta została prob́a weryfikacji hipotezy, izj̇ednym z czynnikoẃ determinujacych dochody indywidualne osob́ aktywnych zawodowo jest stan zdrowia. Przyjeto załozėnie, zė istnieje mozl̇iwosći wpływu zdrowia na obnizėnie dochodoẃ, nie tylko ich całkowita utrate. W analizie wykorzystane zostały mikrodane zgromadzone w ramach badania Diagnoza Społeczna 2009. Oszacowana została funkcja bazujaca na roẃnaniu płac Mincera z logarytmem dochodu osobistego w charakterze zmiennej objasńianej i charakterystykami respondenta (płec\', stazṗracy, wykształcenie, wykonywany zawod́) w charakterze zmiennych objasńiajacych. Przede wszystkim jednak, do modelu właczone zostały zmienne zwiazane ze zdrowiem respondenta. Wyniki badanṕotwierdzaja istnienie pozytywnej zalezṅosći dochodoẃ osob́ aktywnych zawodowo od stanu zdrowia mierzonego jego samoocena. Osoby deklarujace zły stan zdrowia osiagaja dochody przecietnie o 20% nizṡze nizȯsoby, ktoŕe ciesza sie dobrym stanem zdrowia (przy załozėniu, zė pozostałe charakterystyki badanej osoby sa takie same). W przypadku mezċzyzn zalezṅosćd́ochodoẃ od stanu zdrowia jest nieznacznie silniejsza nizẇ przypadku kobiet.
Keywords: 330